Improved breast milk proteome coverage by DIA based LC-MS/MS method - Viitaharju, Jenni; Polari, Lauri; Kauko, Otto; Merilahti, Johannes; Rokka, Anne; Toivola, Diana M.; Laitinen, Kirsi (Wiley-VCH, 2025)
The breast milk composition includes a multitude of bioactive factors such as viable cells, lipids and proteins. Measuring the levels of specific proteins in breast milk plasma can be challenging because of the large dynamic range of protein concentrations and the presence of interfering substances. Therefore, most proteomic studies of breast milk have been able to identify under 1000 proteins. Optimised procedures and the latest separation technologies used in milk proteome research could lead to more precise knowledge of breast milk proteome. This study (n = 53) utilizes three different protein quantification methods, including direct DIA, library-based DIA method and a hybrid method combining direct DIA and library-based DIA. On average we identified 2400 proteins by hybrid method. By applying these methods, we quantified body mass index (BMI) associated variation in breast milk proteomes. There were 210 significantly different proteins when comparing the breast milk proteome of obese and overweight mothers. In addition, we analysed a small cohort (n = 5, randomly selected from 53 samples) by high field asymmetric waveform ion mobility spectrometry (FAIMS). FAIMS coupled with the Orbitrap Fusion Lumos mass spectrometer, which led to 41.7% higher number of protein identifications compared to Q Exactive HF mass spectrometer.